Authority and Ethics of Interpretation in Da'wah Content on Social Media - Hikmawati, Risma (Hadara : Journal of Da'wah and Islamic Civilization, 2025)
Various platforms such as YouTube, Instagram, TikTok, and Twitter (X) are now popular means for both individuals and institutions to convey their understanding of the holy verses. This phenomenon has a positive impact by opening wider access and encouraging community involvement in religious discourse. However, this openness also presents serious challenges. A crisis of authority, accuracy issues, and ethics in the presentation of interpretations have emerged. This study attempts to analyze the standards of authority of interpretation and complement them with ethical concepts (in this case using the ethical concept of Da'I KH. Bisri Mustofa) that can be implemented into ethical, authoritative and authentic standards, especially for da'wah content on social media containing interpretations of the Qur'an. This study uses a qualitative method with a library research approach. The results obtained are that the wetness of the interpretation follows the standard of interpretation authority that has been formulated by scholars of interpretation and pays attention to the ethics of preaching in the production of interpretation in social media preaching content into two inevitability.